A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus - Chen, Zhi-Teng; Song, Liang-Dong; Feng, Wen-Tao (Zootaxa, 2019)
A new species of the perlodid genus Isoperla Banks, 1906, Isoperla qinlinga Chen, sp. nov. from Shaanxi Province of northwestern China is described. The new species is characterized by the mostly dark head and pronotum, the poorly developed vesicle, the modified ventral and dorsal aedeagal lobes, and the slightly developed, rounded subgenital plate of the female. Comments are provided on the known species of Isoperla of China.